Determinants of the Demand for Manpower Training : Some Empirical Results - Truesdell, L. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1975)
The author develops a short-run model for the demand of manpower training. It is shown that the short-run demand for manpower training is sensitive to the levels of unemployment as well as to seasonal factors. Various functional forms are also investigated